Diet and brood size in rural and urban Northern Goshawks Accipiter gentilis in southern Finland. (February 2019) - Solonen, Tapio; Lokki, Heikki; Sulkava, Seppo
The brood size in the Finnish Northern Goshawks seems to be associated with the breeding habitat and the availability of suitable prey. In this study, we examined these relationships in three study areas of different landscape structure in southern Finland, including a recently colonized urban area. The most abundant prey categories found in the food remains of the goshawk included corvids, turdids, columbids, gallinaceous birds, and squirrels. Corvids dominated in the diet samples of all the study areas. The number of turdids and columbids in the samples was significantly higher in both the rural and the urban habitats than in the wilderness area. The number of gallinaceous birds was significantly higher in the wilderness area than in other habitats. Gallinaceous birds, particularly tetraonids, the traditional staple food of the Northern Goshawk in Finland, seemed to be largely compensated by corvids in the wilderness area and by corvids and columbids in the rural and urban areas. The amount of corvids in prey showed a positive relationship with brood size, suggesting some particular importance of this prey in the goshawk diet. In all, diet seemed to explain partly between-landscape variations in the brood size of the goshawk. The brood size was significantly higher in the urban landscape than elsewhere.